Millet based multigrain mix: its physico chemical properties and value addition- a review - Khatoniar, Sushmita; Das, Pranati (Journal of Postharvest Technology, 2022)
Millets are now-a days considered as superfoods as they contain numerous health protective factors including dietary fibre, phytochemicals  and antioxidant properties. The goodness of millets can be combined with other commonly consumed flours such as whole wheat flour to  make it nutritionally superior. The concept of multigrain mixes is gaining attention as one grain can supplement the nutrients that are lacking in  the other grains. These multigrain mixes can be utilized in development of diversified food products like bakery and puffed products, quick  cooking cereals, ready-to-eat snacks, supplementary foods, weaning foods, and more importantly health foods. The present study is aiming on  review of work done on the formulation, physico-chemical evaluation of millet based multigrain mixes and value-added products prepared  using millet based multigrain mixes.
Keywords: Millets,; multigrain; antioxidants; dietary fibre; micronutrients